Side Effect Of 5-Hydroxytriptamine Receptor Antagonist In The Prophylactic Treatment Of Emesis Induced By Cisplatin And Taxotere Chemotherapy A Case Report. - Djunaedi, Mochamad; Mohd Yussof, Zuraidah; Othman, Saad (2006)
The 5-hydroxytryptamine3 receptor (5-HT3receptor) antagonists recently has been developed as a class of new anti-emetic agent.